Experimental study on the effect of metal foams pore size in a phase change material based thermal energy storage tube. (25th November 2022) - Righetti, Giulia; Zilio, Claudio; Longo, Giovanni A.; Hooman, Kamel; Mancin, Simone
Highlights: The use of a metal foam reduces the charging and the discharging times of about 10 and 5 times. A tube-in-tube heat exchanger was used as latent thermal energy storage. The pore density, the inclination, and the water inlet condition effects were investigated. The inclination angle does not affect the phase change times when a foam is used. Abstract: It is well known that latent thermal energy storages can help in store large quantities of energy in small volumes, but that their charging and discharging periods are prohibitively long. In this work it was experimentally demonstrated that the addition of a foam can drastically shorten the phase change materials charging and discharging times up to 10 and 5 times, respectively. A tube-in-tube heat exchanger, where water flows in the tube with an aluminum foam-saturated Phase Change Material inserted in the annulus, was experimentally tested and new data was added to the open literature. Testing three different foam samples, the influence of the foam pore density (10, 20, and 40 Pores per Inch), sample orientation as well as that of water flow rate (from 2 to 8 l min −1 ) and inlet temperature (from 45 to 55 °C), on charging and discharging processes was investigated. Few researchers investigated the influence of sample orientation, while published results do not agree on the pore size influence. In this work it was found that the 20 Pores per Inch sample showed the best performance leading to fastest charging and discharging processes. Moreover, it was observed that with foam-saturated Phase Change Materials, the charging and discharging times are not affected by the inclination angle. On the contrary, they are affected by water flow rate and temperature. A high inlet water temperature and a high water flow rate can shorten both phase transfers.